PENINGKATAN PEMAHAMAN VMTS UNTUK SEKOLAH EFEKTIF BERBASIS COACHING - Adliroh; Ardhani, Rina; Setianingrum, Ratih; Ari Teliti Wilarsati; Ngurah Ayu Nyoman Muniarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Effective school is a strong relationship between what has been formulated to be done and the results achieved by the school. Educational units need to have a clear and measurable vision, mission, goals, and objectives (VMTS). However, not all components of the education unit or stakeholders have the same understanding of the VMTS. This article discusses an experiment to equalize the understanding of VMTS to achieve effective schools through coaching methods with teachers who interact directly with students. Through the application of coaching methods, teachers feel more comfortable and easier to receive information on formal topics such as VMTS. After 2 weeks of implementation, there are developments in teacher administration in learning.